Social economy as an important link in the family support system - Jagielska, Katarzyna; Matejek, Józefa (Social Entrepreneurship Review, 2020)
Issues related to the transformation of modern family are one of the important problems in the field of social policy. This article focuses on the problems arising from demographic change – particularly the ageing of the population, which consequence is the increasing importance of the family’s caring role to its oldest members. Social economy plays an important role in this area, becoming an important factor in the family help and support system. Social enterprises can support families by providing care services for the elderly. This is an important aspect in the case of the ageing of Polish society. With age, functional capacity decreases, and multiple diseases develop. This results in an increasing demand for care services for the elderly. Services dedicated to seniors under the social welfare and health care systems do not meet the needs for all those who need them. Therefore, a need to look for new solutions in this area exists.